2012
DOI: 10.1111/j.1863-2378.2012.01456.x
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Japanese Encephalitis Virus and Risk Factors Associated with Seropositivity in Pigs in Four Mountain Districts in Nepal*

Abstract: Japanese encephalitis was recently reported from individuals in the mountain districts of Nepal without travel history to Japanese encephalitis virus (JEV) endemic areas. We performed a cross-sectional study to estimate the seroprevalence of JEV in pigs and subsequently conducted a survey of farmers to identify risk factors associated with seropositivity. In July and August, 2010, 454 pig serum samples were collected and tested by competitive ELISA. Data from a 35-question survey of 109 pig owners were analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 36 publications
(56 reference statements)
1
18
2
Order By: Relevance
“…The prevalence rate observed in this study was less than the previous report from various 10 (Pant, 2006) and another research including 16 districts which showed 55% prevalence (Pant et al, 2006). One cross sectional study conducted from July to August of 2010 in Sindhupalchowk, Dolakha, Solukhumbu and Kavrepalanchowk had shown 16.7% prevalence in Sindhupalchowk, 4% prevalence in Dolakha, 6.6% in Solukhumbu and 44.6% prevalence in Kavrepalanchowk (Thakur et al, 2012). The findings of this study are almost comparable to the findings from other Asian countries like 49% in Bali and 6% in Java of Indonesia (Yamanaka et al, 2010); 33.3% in Tibet (Li et al, 2009) and 4.5% in Ishigaki Island, Japan (Nidaira et al, 2009).…”
Section: Comparison Of Swine Sero-statuscontrasting
confidence: 76%
“…The prevalence rate observed in this study was less than the previous report from various 10 (Pant, 2006) and another research including 16 districts which showed 55% prevalence (Pant et al, 2006). One cross sectional study conducted from July to August of 2010 in Sindhupalchowk, Dolakha, Solukhumbu and Kavrepalanchowk had shown 16.7% prevalence in Sindhupalchowk, 4% prevalence in Dolakha, 6.6% in Solukhumbu and 44.6% prevalence in Kavrepalanchowk (Thakur et al, 2012). The findings of this study are almost comparable to the findings from other Asian countries like 49% in Bali and 6% in Java of Indonesia (Yamanaka et al, 2010); 33.3% in Tibet (Li et al, 2009) and 4.5% in Ishigaki Island, Japan (Nidaira et al, 2009).…”
Section: Comparison Of Swine Sero-statuscontrasting
confidence: 76%
“…In addition, other climate-sensitive vector-borne diseases, including malaria, lymphatic filariasis, visceral leishmaniasis and dengue, have been reported in the hilly and mountain regions of Nepal, which were previously considered as non-endemic, indicating the adaptation of vectors in non-endemic regions [30, 31]. The study also detected anti-JE virus antibodies in swine populations sampled from four high-altitude mountain districts of Nepal indicating circulation of JE virus, where human infections were documented [32]. Similarly, a study conducted by Impoinvil et al (2011) demonstrated JE clusters shifting to hilly and mountain regions of Nepal [26].…”
Section: Discussionmentioning
confidence: 74%
“…A significantly positive association of JE incidence with monthly temperature and the percentage of irrigated land, and a negative association with low precipitation has also been reported from Nepal [81]. The spatiotemporal distribution of JE cases in Nepal (1978–2012) is shown in Fig 6[77,79,80,81,82,107]. …”
Section: Resultsmentioning
confidence: 80%
“…It was first recorded in Nepal in 1965 with a distribution ranging from the lowland to hill regions including Kathmandu valley [60]. Although most reported JE cases in Nepal were initially confined to 24 districts in the lowland Terai [78], JEV transmission is now established in hill and mountain districts of Nepal, including Kathmandu valley, which were previously considered non-endemic for this disease [77,79,80,81,82]. Moreover, there are reports of spatial cluster of JE incidence with a shift from the Terai lowlands to hill and mountain regions after 2005 [81].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation